Adsorption Characteristics and Mechanism of Bisphenol A by Magnetic Biochar - Wang, Jinpeng; Zhang, Ming (International journal of environmental research and public health, 2020)
In this paper, biochar (BC) was prepared from discarded grapefruit peel and modified to prepare magnetic biochar (MBC). Physical and chemical properties of BC and MBC were characterized, and the results showed that the type of iron oxide loaded by MBC was γ-Fe2O3. Compared with BC, MBC has a larger specific surface area and pore volume, with more oxygen-containing functional groups on the surface. BC and MBC were used to adsorb and remove endocrine-disrupting chemical (EDC) bisphenol A (BPA) from simulated wastewater. The results showed that the adsorption kinetics and adsorption isotherm of BPA adsorption by BC and MBC were mainly in accordance with the pseudo-second-order kinetics model and the Langmuir model. This indicates that the adsorption of BPA on BC and MBC is mainly a chemically controlled monolayer adsorption. Adsorption thermodynamics show that BC and MBC adsorption of BPA is a spontaneous exothermic reaction, and lowering the temperature is conducive to the adsorption reaction. The effect of solution pH on the adsorption of BPA by both was significant. The optimum pH for BC and MBC to absorb BPA was 6 and 3, respectively. The concentration of Na+ in the range of 0–0.10 mol·L−1 can promote the adsorption of BPA to MBC. MBC loaded with γ-Fe2O3 not only has excellent magnetic separation ability, but can also reach about 80% of the initial adsorption capacity after four cycles of adsorption. By analyzing the adsorption mechanism, it was found that the H-bond and the π–π electron donor–acceptor interaction (EDA) were the main forces for BC and MBC to adsorb BPA.